Synthesis and characterization of the biodegradable and elastic terpolymer poly(glycolide-co-L-lactide-co-epsilon-caprolactone) for mechano-active tissue engineering - Jung, Youngmee; Lee, Sun-Hee; Kim, Sang-Heon; Lim, Jong Choo; Kim, Soo Hyun (TAYLOR & FRANCIS LTD, 2013)
We synthesized a series of tri-component biodegradable copolymers with elastic characteristics by ring-opening copolymerization of cyclic lactones, that is, glycolide, L-lactide, and E-caprolactone, in the presence of stannous octoate as a catalyst. We evaluated the physical and chemical characteristics of poly(glycolide-co-L-lactide-co-E-caprolactone) (PGLCL) copolymers. The synthesized PGLCL had a high molecular weight of about 100kD and an amorphous structure. It was confirmed that the physical and chemical properties of these terpolymers could be modulated by adjusting copolymer composition. PGLCL films exhibited rubber-like elasticity and showed almost complete recovery when subjected to 50% of the tensile strain. To examine the biodegradability of the PGLCL copolymers, we performed in vitro degradation tests for 12weeks and observed changes in molecular weight, gross weight, and composition. These results showed that the glycolide was degraded most quickly and that E-caprolactone was the slowest to degrade. Additionally, cytotoxicity tests revealed that none of the polymers were toxic. In summary, the mechanical properties and biodegradability of PGLCL terpolymers could be controlled by changing the monomer content, which may be useful for a wide range of tissue engineering applications based on mechanical property requirements.
Keywords: RING-OPENING POLYMERIZATION; IN-VITRO DEGRADATION; EPSILON-CAPROLACTONE; L-LACTIDE; COPOLYMERS; GLYCOLIDE; SCAFFOLD; POLY(L-LACTIDE-CO-EPSILON-CAPROLACTONE); REGENERATION; COLLAGEN